Program pro poloautomatické histomorfometrické vysetrení kostních biopsiíi - Prokop, M; Povýsil, C; Hrbek, V (Ceskoslovenska patologie, 1989)
A simple semiautomated system for evaluation of histomorphometric parametres in bioptic bone sections was designed in cooperation of programmer and a pathologist. It saves time and effort of pathologist substantially and shows a relative numerical precision. It is based on digitalization of microscopical picture projected on a desk and computerized processing of digitalized picture.
Keywords: Software; software; kosti a kostní tkáň; lidé; počítačové zpracování obrazu; Bone and Bones; Biopsy; Image Processing, Computer-Assisted; biopsie; Humans